2015
DOI: 10.1002/cae.21658
|View full text |Cite
|
Sign up to set email alerts
|

A computer simulation in mechanics teaching and learning: A case study in circular motions

Abstract: A computer simulation program has been developed and is used in teaching and learning for circular motions. The program can illustrate a moving particle with its position, velocity, and acceleration. It can also draw the angular position‐time figure, angular velocity‐time figure, and angular acceleration‐time figure. Students were divided into 4 groups: A, B, C, and D. Group A used only traditional teaching methods without computer simulations. Group B used 20% of class time to see demos of the computer simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…We did not face the issue reported in reference , where the students did not know how to use the program (games in our case). The possible reason is that we included an introduction to how to play at the beginning of each game.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We did not face the issue reported in reference , where the students did not know how to use the program (games in our case). The possible reason is that we included an introduction to how to play at the beginning of each game.…”
Section: Discussionmentioning
confidence: 92%
“…No quantitative results were reported, but the author qualitatively observed that the interest and understanding on the subject were improved. Lee and Hwan developed a computer simulation program to teach circular motions and conducted detailed comparisons. They concluded that most students did not know how to learn from simulation by themselves, while they can learn more from a demo controlled by the instructors.…”
Section: Introductionmentioning
confidence: 99%
“…When physical problems require a complex mathematical formulation, the numerical approaches are straightforward procedures and the computer simulation became a very convenient teaching tool to help students visualizing the solutions [20]. Such connection between quantum mechanics description and computer simulation is clearly stated [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, improving the teaching‐learning process includes expanding the technology used for developing computer simulations and providing rapid access to the virtual physics laboratory. Furthermore, in the last three decades computer simulations have become compulsory and powerful devices in educational process because they are able to support educational activities such as easy learning and the study of various physical laws and phenomena .…”
Section: Introductionmentioning
confidence: 99%